Conjunctival bacterial and fungal flora in clinically normal sheep. Issue 1 (10th June 2014) - Bonelli, Francesca; Barsotti, Giovanni; Attili, Anna Rita; Mugnaini, Linda; Cuteri, Vincenzo; Preziuso, Silvia; Corazza, Michele; Preziuso, Giovanna; Sgorbini, Micaela
Abstract : Objectives: The aim was to identify conjunctival bacterial and fungal flora in clinically normal sheep. Design: Prospective study. Setting: Tuscany. Participants: 100 eyes from 50 adult Massese female sheep were examined. The sheep included in the study were considered free of anterior ophthalmic abnormalities. Primary and secondary outcome measures: Bacteria were identified by morphological assessment, Gram staining, biochemical tests. Identification of filamentous fungi was achieved at the genus level, and Aspergillus species were identified based on keys provided by other authors. Yeast colonies were highlighted, but not identified. Results: Positive cultures were obtained from 100/100 eyes for bacteria, and from 86/100 eyes for fungi. A total of 14 types of bacteria and 5 types of fungi were isolated. Yeasts were isolated from 13/100 eyes. The most frequent fungal isolates were saprophytic fungi. Conclusions: Conjunctival bacterial and fungal flora of clinically normal eyes were reported in sheep. The positivity obtained for conjunctival bacteria was higher compared to findings in the literature by other authors in the same species (100 per cent v 40 per cent), while our results were in line with a recent work performed on mouflons ( Ovis Musimon ) with a 100 per cent positivity for bacterial conjunctival fornix. In our survey, Gram‐positive species were prevalent, as reported by other authors in different species. Few data are available in the literature regarding conjunctival fungal flora in healthy small ruminants. The prevalence of conjunctival fungal flora in this study was higher than findings reported in mouflons (86 per cent v 45 per cent). Differences in fungal prevalence may be due to different methods of managing herds, though further studies are required to verify this hypothesis. The similarities in bacterial and fungal isolates between sheep and mouflons suggest a genera pattern of conjunctival colonisation by bacteria and fungi.